The immunopathogenesis of Helicobacter pylori-induced gastric cancer: a narrative review - Shirani, Maryam; Shariati, Saeedeh; Bazdar, Monireh; Sojoudi Ghamnak, Faezeh; Moradi, Melika; Shams Khozani, Reyhane; Taki, Elahe; Arabsorkhi, Zahra; Heidary, Mohsen; Eskandari, Dorsa Bahrami (Frontiers in Microbiology, 2024)
Helicobacter pylori (H. pylori) infection is a well-established risk factor for the development of gastric cancer (GC). Understanding the immunopathogenesis underlying this association is crucial for effective preventive and therapeutic strategies. This narrative review comprehensively explores the immunopathogenesis of H. pylori-induced GC by delving into several key aspects, emphasizing the pivotal roles played by H. pylori virulence factors including cytotoxin-associated gene A (cagA) and vacuolating cytotoxin A (vacA), blood group antigen-binding adhesin (babA) as well as sialic acid binding adhesin (sabA). Moreover, the review focuses on the role of Toll-like receptors (TLRs) and cytokines in the complex interplay between chronic infection and gastric carcinogenesis. Lastly, the article examines the association between H. pylori evasion of the innate and adaptive immune response and development of GC (GC). A comprehensive understanding of the immunopathogenesis of H. pylori-induced GC is essential for designing targeted interventions to prevent and manage this disease. Further research is warranted to elucidate the intricate immune responses involved and identify potential therapeutic targets to improve patient outcomes.